The effect of Citrus sinensis peel extract against Rhipicephalus sanguineus (Dog Ticks) - Armugam V.,; Sundraraj Y.A.,; Saleh I., (Malaysian Society of Applied Biology, 2016)
Tick transmitted disease remains a major source of illness and death worldwide. Many chemical agents have been employed to control ticks. They are normally safe, but some of them may be responsible for toxic reaction in animals, reduced effect in the long run due to development of resistant strains of ticks, environmental pollution and human health hazards. Agricultural waste such as Citrus sinenesis peel has been exploited and highly potential as anti-tick. The purpose of this study is to assess the effect of Citrus sinensis peel extract against Rhipicephalus sanguineus commonly known as dog ticks. Sample sizes of 400 larval were obtained by tick breeding. Extraction of Citrus sinensis peels extract was obtained through two methods; heat press extraction and cold press extraction. For each method, the larvae were tested on 50%, 75% and 95% concentrations. Effect was measured in terms of tick mortality rate and rapidity of action. Maximum effect was found at 95% strength from samples obtained using the heat press method which shows 98% tick mortality rate with P < 0.05. The final results validated the insecticidal properties inherent in heat press Citrus sinensis peel extract.